Convergent evolution inspired serrated structure for improving efficiency of soil imprinting and its mechanism investigation - Zhang, Zhihong; Li, Ying; Tong, Jin; Carr, Stephen (International Journal of Agricultural and Biological Engineering, 2019)
Remarkable geometrical similarities are found in digging claws of soil burrowing animals, in spite of the fact that they evolved independently. Based on convergent evolution theory, this study innovatively proposed a bionic engineering perspective that focuses on general and analogous geometrical characteristics of soil animals. It was observed that soil animals with powerful burrowing ability have analogous serrated structures on their digging claws. Taking soil imprinting toothed wheel as the research object, the hypothesis that special serrated structures have the potential of reducing penetrating resistance from soil and enhancing digging efficiency for soil engaging component was investigated. The convergent evolution inspired bionic serrated structures were utilized for the design of cutting edge on toothed wheel. Then, a toothed wheel that mounted with the conventional tooth and a bionic tooth were manufactured and tested in the soil bin. Results showed that special bionic serrated structure could reduce the required draft force for toothed wheel; meanwhile increase the depth and volume of prepared micro-basin. It was found that the soil-penetrating mechanism of the bionic toothed wheel behaved as saw cutting that similar to the digging behavior of soil burrowing animals. Geometry of serrated structure has the ability to maximum stress concentrations in soil, thus increased the tendency of soil material to fail. These results indicate that the convergent evolution inspired bionic approach is novel and advantageous for the design of new soil engaging implements for working quality optimization and forward resistance reduction.Keywords: convergent evolution, bionic serrated structure, soil imprinting, soil-engaging component, bionic agricultural machineryDOI: 10.25165/j.ijabe.20191204.3638Citation: Zhang Z H, Li Y, Tong J, Carr S. Convergent evolution inspired serrated structure for improving efficiency of soil imprinting and its mechanism investigation. Int J Agric & Biol Eng, 2019; 12(4): 16–26.